0839 A Prospective Investigation Of Bidirectional Relationships Between Sleep Duration And Obesity. (12th April 2019) - Daghlas, Iyas; Dashti, Hassan S; Rutter, Martin K; Scheer, Frank A J L; Saxena, Richa; Vetter, Céline
Abstract: Introduction: Associations between sleep duration and obesity have been mixed, and have predominantly focused on body mass index (BMI) rather than measures of abdominal obesity such as waist-hip ratio (WHR). Furthermore, it is unclear whether and to what extent body composition affects sleep duration. We aimed to clarify these relationships using a large prospective study design. Methods: We analyzed data from UK Biobank participants at baseline (n1 =458, 877) and up to two follow-up assessments (n2 =20, 139, n3 =4, 073). We estimated the association of habitual, self-reported sleep duration (hours/day) with cross-sectional and prospective changes in BMI and WHR, adjusting for confounders and sleep traits. We then investigated whether baseline BMI or WHR associated with change from normal (7-8 hours) to short (<7 hours) or long (>8 hours) sleep duration at follow-up. Results: Short and long sleep duration were associated with higher BMI and WHR at baseline, but short sleep was not associated with WHR after adjusting for BMI. Significant increases in BMI after 4.4 years of follow-up were only observed amongst participants sleeping four hours per night (0.56kg/m 2, 95% confidence interval 0.23-0.90, p=0.0011). Associations were less consistent for the change in WHR, and were null when considering all three time points in linear mixed-effects models. Long sleep duration was not associated with changes in weight outcomes. In reverse association, we observed that amongst individuals with normal sleep duration, a one-standard deviation (SD) higher BMI at baseline was associated with becoming either a short (OR=1.08, CI 1.02-1.14) or a long (OR=1.14, 1.06-1.22) sleeper at follow-up, and a one-SD higher WHR was associated with becoming a long sleeper at follow-up (OR=1.16, 1.06-1.28). Conclusion: Sleep duration of four hours per night, reported by a small proportion of the population, was a risk factor for increases in BMI, but not for abdominal adiposity. Reverse causality potentially impacts associations of sleep duration with obesity, and weight loss should be investigated as a strategy to improve sleep health. Support (If Any): R01DK105072 (RS, FAJLS), R01DK107859 (RS, HSD), The University of Manchester Research Infrastructure Fund (MKR)